Causes of Cretaceous Oceanic Anoxic Events (OAEs) - Zhang, Chengjun (International Journal of Natural Resources and Environmental Studies, 2026)
Oceanic Anoxic Events (OAEs) during the Cretaceous—designated OAE1, OAE2, and OAE3, with OAE1 further subdivided into OAE1a, OAE1b, OAE1c, and OAE1d—are widely attributed to volcanic activity from the Kerguelen, Ontong Java, and Caribbean Large Igneous Provinces (LIPs), which triggered at least two global OAEs. These events are characteristically marked by widespread deposition of organic‑rich black shales and positive carbon isotope excursions. By systematically reviewing the geochemical behavior of molybdenum (δ98Mo) and zinc (δ66Zn) isotopes, we find that δ98Mo primarily tracks the transition between locally euxinic and non‑euxinic conditions, whereas δ66Zn serves to distinguish different responses of local marine systems—including primary productivity, continental weathering, and sediment burial/decomposition. Nevertheless, the fractionation mechanisms governing these metal stable isotopes in the oceanic realm remain incompletely understood, and existing records focus predominantly on OAE2. Future research must therefore adopt a more comprehensive and systematic approach across all OAEs.